Yield Grade and Quality Assessment of Native Buffalo Meat and Beef at Different Ages - Roy, B. K.; Huda, N.; Huque, K. S.; Sultana, N.; Sarker, N. R. (Tropical Animal Science Journal, 2020)
Boosting meat production potential possibly happens when people will judge meat quality and use their livestock wisely, as they meet up their demand from promising animal like buffalo. To evaluate the productive performances and quality assessments of beef and buffalo meats, cattle (Pabna) and buffalo (Native, swamp type) were fattened for 120 days with a single plane of nutrition in a 2×3 (Species×Age) factorial experiment. By slaughtering, the carcass and non-carcass characteristics, primal cuts, pH, drip loss, cooking loss, color, intramuscular fat of meat, marbling score, and yield grade of meat were determined through univariate GLM procedure based CRD analysis. Live and carcass weights of buffalo were significantly higher (p